CREDIT COOPERATIVISM IN BRAZIL: INSTITUTIONAL TENSIONS BETWEEN MUTUALITY, GOVERNANCE, AND MARKET PRESSURES - Golos, Otávio Augusto (Seven Editora, 2026)
This study analyzes the trajectory of credit cooperativism in Brazil, focusing on the tensions between mutuality, governance, and market pressures that shape its contemporary evolution. The research employs a qualitative approach, combining analytical-descriptive narrative review with documentary analysis of institutional reports and specialized literature. Data show that the sector grew by 86% in the number of members between 2019 and 2024, with total assets exceeding R 885 billion and presence in 58% of Brazilian municipalities, consolidating itself as an alternative to the traditional banking system. The analysis identifies three critical axes: (i) mutuality vs. efficiency, highlighting democratic governance and surplus distribution; (ii) regulatory and market pressures, which pose challenges to the cooperative identity; and (iii) socioeconomic impact, particularly in regions with low banking capillarity. The discussion incorporates recent sources to problematize the sustainability of the model in the face of management professionalization and increasing operational complexity. The findings demonstrate that, while credit cooperativism presents concrete competitive advantages, its accelerated growth requires balancing efficiency with the preservation of principles. The research concludes that the institutional stability of the sector depends on the ability to expand scale without undermining mutuality, proposing an agenda for future studies on best governance practices in large cooperatives.